Changes in Gene Expression within the Ventral Tegmental Area Following Repeated Excessive Binge-Like Alcohol Drinking by Alcohol-Preferring (P) Rats - McBride, William J. (2013)
The objective of this study was to detect changes in gene expression in the ventral tegmental area (VTA) following repeated excessive binge-like (‘loss-of-control’) alcohol drinking by alcohol-preferring (P) rats. Adult female P rats (n = 7) were given concurrent access to 10, 20, and 30% EtOH for 4 1-hour sessions daily for 10 weeks followed by 2 cycles of 2 weeks of abstinence and 2 weeks of EtOH access. Rats were sacrificed by decapitation 3 hours after the 4(th) daily EtOH-access session at the end of the second 2-week relapse period. A water-control group of female P rats (n = 8) was also sacrificed. RNA was prepared from micro-punch samples of the VTA from individual rats; analyses were conducted with Affymetrix Rat 230.2 GeneChips. Ethanol intakes were 1.2–1.7 g/kg per session, resulting in blood levels > 200 mg% at the end of the 4(th) session. There were 211 unique named genes that significantly differed (FDR = 0.1) between the water and EtOH groups. Bioinformatics analyses indicated alterations in a) transcription factors that reduced excitation-coupled transcription and promoted excitotoxic neuronal damage involving clusters of genes associated with Nfkbia, Fos, and Srebf1, b) genes that reduced cholesterol and fatty acid synthesis, and increased protein degradation, and c) genes involved in cell-to-cell interactions and regulation of the actin cytoskeleton. Among the named genes, there were 62 genes that showed differences between alcohol-naïve P and non-preferring (NP) rats, with 43 of the genes changing toward NP-like expression levels following excessive binge-like drinking in the P rats. These genes are involved in a pro-inflammatory response, and enhanced response to glucocorticoids and steroid hormones. Overall, the results of this study indicate that the repeated excessive binge-like alcohol drinking can change the expression of genes that may alter neuronal function in several ways, some of which may be deleterious.